Emergency Service Response Plan for Covid-19 Pandemic in Resource Limited Settings - Maharjan, Ramesh Kumar; Shrestha, Jukel; Shakya, Yogendra Man; Aacharya, Ramesh Prasad; Prasad, Pratap Narayan (Tribhuvan University Journal, 2020)
Emergency workers carry a huge responsibility in Covid 19 pandemic. Emergency staff have to provide prehospital care, early triage and management of patients with suspected or confirmed infection. More importantly, emergency care givers have to do everything to prevent emergency room from spread of the infection, to other patients. Access blocks following increasing flow of patients with suspicion of infection, causes overwhelming patients leading to delayed care and resource shortage to patients with chronic and acute diseases. This surge has put emergency workers at risk: risk from a potential contamination and risk from the effect of extended shifts work in the hospital. At this stage, the major challenges while performing emergency service has been managing triage, human resources, limited stock of personal protective equipment (PPE), proper management of infection prevention and limited laboratories for testing.Due to lack of those requirements, certain guidelines and running the service without such guidelines making the emergency service in difficult situation during such crisis period.